Langkah-Langkah Tafsir Maudu’i - Asep Mulyaden; Asep Fuad (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the steps of Maudu'i interpretation of the Qur'an. This method has steps in interpreting the Qur'an, and usually responds to the challenges of the times, is more practical, systematic, dynamic and easy to understand in its entirety by the general public. This method is relatively new and is considered actual in interpreting the Qur'an departing from a logical unity and interrelated with one another. The method used in this research is descriptive, a research method that seeks to analyze and describe something, such as existing conditions or relationships, developing opinions, and or ongoing processes. Based on this method, in this study, the author will attempt to reveal experts' understanding regarding the steps of maudu'i interpretation. From this theory, it can be seen that to get a complete understanding of the Qur'an according to a certain theme, we must take certain steps, starting from choosing or determining the topic of the Qur'an in a maudhu`i manner, collecting verses that relating to this problem, coherently compiling the verses according to the chronology of their descent, knowing the correlation (munasabah) of these verses in each letter, arranging the theme of discussion in an appropriate framework, completing the discussion and description with the hadith, and study the verses thematically and thoroughly.